(untitled) (Jurnal Adabiya, 2020)
AMIKOM STMIK Library Yogyakarata is a library that has implemented a digitization system. All forms of library access are presented in digital form, ranging from book collections, journals, to the use of several other digital services. So that collections from digital libraries can be used for a long time, a library needs to do digital preservation. This study aims to see how the strategy of the STIKIK AMIKOM library in Yogyakarta to preserve digital collections. This research method uses descriptive qualitative and data collection using interviews. The research results in this study are the AMIKOM STMIK library doing several activities such as; preservation and refreshing of digital devices and also backing up digital collections.